2014
DOI: 10.1111/jch.12451
|View full text |Cite
|
Sign up to set email alerts
|

Digital Plethysmography and Arginine Metabolism in Prehypertension—Effect of Nebivolol Therapy

Abstract: Prehypertension is an important phenotype for cardiovascular risk and development of established hypertension. To better understand the early circulatory changes in this group, the authors studied 34 patients with prehypertension (blood pressure 120-139/80-89 mm Hg) using digital plethysmography for measurement of blood flow and reactive hyperemic index (RHI). Arterial augmentation index (AI) was also measured. Because prehypertension is associated with endothelial dysfunction and decreased availability of nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
4
1
1
Order By: Relevance
“…In addition, different classes of antihypertensive drugs have different effects on the central BP and arterial stiffness . However, the current study did not show any beneficial effect of nebivolol treatment on AI despite reductions in BP . Vaz‐de‐Melo and colleagues demonstrated that nebivolol reduced central BP but not AI.…”
contrasting
confidence: 59%
See 2 more Smart Citations
“…In addition, different classes of antihypertensive drugs have different effects on the central BP and arterial stiffness . However, the current study did not show any beneficial effect of nebivolol treatment on AI despite reductions in BP . Vaz‐de‐Melo and colleagues demonstrated that nebivolol reduced central BP but not AI.…”
contrasting
confidence: 59%
“…In this issue of The Journal of Clinical Hypertension , Kandavar and colleagues studied the circulatory changes in prehypertensive patients by digital plethysmography for measurement of blood flow and reactive hyperemic index (RHI). Additionally, they measured augmentation index (AI) and the effect of nebivolol therapy on L‐arginine, asymmetric dimethlyarginine (ADMA), symmetric dimethlyarginine (SDMA), and L‐citrulline levels after 8 weeks in a blinded fashion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Это было пока-зано методами измерения реактивного гиперемиче-ского индекса и среднего давления в артериях паль-цев. Такой эффект объясняло повышение циркулирующих в крови уровней 1-цитрулина и асимметричного диметиларгинина [6]. Davis et al (2013) также исследовали лиц с предгипертензией.…”
Section: плейотропные эффекты небиволола: новые данныеunclassified
“…12,13 Unfortunately, calcineurin inhibitors (CNIs), the cornerstone of current antirejection immunosuppression, can negate these beneficial effects through various mechanisms including elaboration of vasoconstrictor cytokines and reduction in vasodilator prostaglandins and NO. 3,5,[17][18][19][20] CNIs are also implicated in the pathogenesis of posttransplant hypertension through activation of the sympathetic nervous and renin-angiotensin-aldosterone systems, intense afferent arteriolar vasoconstriction, and sodium retention. [21][22][23] In the absence of a robust, evidence-based guideline on the management of post-transplant hypertension, 11,24 clinicians have a wide latitude in selecting drugs for treating hypertension in transplant recipients.…”
mentioning
confidence: 99%